Предмет: Алгебра,
автор: kazarianroz
Помогите пожалуйста решить уравнение под номером 3)
Приложения:
Ответы
Автор ответа:
0
10^x + 10^(x-1) = 0.11
10^x + 10^x - 10^(-1) = 0.11
(Выносим общий)
10^x * ( 1 + 10^(-1) ) = 0.11
10^x * ( 1 + 0.1 ) = 0.11
10^x * ( 1.1 ) = 0.11
10^x = 0.1
10^x = 10^(-1)
x = -1
10^x + 10^x - 10^(-1) = 0.11
(Выносим общий)
10^x * ( 1 + 10^(-1) ) = 0.11
10^x * ( 1 + 0.1 ) = 0.11
10^x * ( 1.1 ) = 0.11
10^x = 0.1
10^x = 10^(-1)
x = -1
Похожие вопросы
Предмет: География,
автор: nilaty
Предмет: Литература,
автор: vavruniukvicka
Предмет: Русский язык,
автор: samirrazmatov3
Предмет: Литература,
автор: pomorde2
Предмет: Алгебра,
автор: супердевочка1